STUDY ON THE COST OF USING DIGITAL AGRICULTURE APPLICATIONS AT PT PALMCO KEBUN ADOLINA AFDELING II - Amalia Istiqomah; Tuty Ningsih (Jurnal Mahasiswa Agribisnis, 2026)
The rapid advancement of digital technology has encouraged oil palm plantation companies to adopt digital farming systems to improve operational efficiency, data accuracy, and transparency in production management. This study aimed to analyze the cost of using digital agriculture applications in the Fresh Fruit Bunches (FFB) input process at PT PalmCo Kebun Adolina Afdeling II, North Sumatra. A quantitative descriptive method was employed using observation, interviews, and operational data records. The cost components analyzed included depreciation costs, maintenance costs, internet data package costs, and labor costs. The results showed that the total cost of implementing the digital agriculture application was IDR 30,263,363.86 for a total FFB production of 1,541,600 kg, resulting in a cost of IDR 19.63 per kilogram of FFB. Labor costs represented the largest proportion of total expenses, while depreciation, maintenance, and data package costs contributed relatively small amounts. The application improved the speed, accuracy, and transparency of FFB production recording and reporting processes. These findings indicate that digital agriculture applications can support efficient plantation operations and provide reliable real-time production data for managerial decision-making, thereby supporting digital transformation in the oil palm plantation industry. Keywords: Digital agriculture, operational costs, palm oil, FFB, digitalization.